Stochastic Second-Order Two-Scale Method for Predicting the Mechanical Properties of Composite Materials with Random Interpenetrating Phase (Communications in Mathematical Research, 2022)
In this paper, a stochastic second-order two-scale (SSOTS) method isproposed for predicting the non-deterministic mechanical properties of composites with random interpenetrating phase. Firstly, based on random morphology description functions (RMDF), the randomness of the material properties of the constituents as well as the correlation among these random properties is fully characterized through the topologies of the constituents. Then,by virtue of multiscale asymptotic analysis, the random effective quantitiessuch as stiffness parameters and strength parameters along with their numerical computation formulae are derived by a SSOTS strategy combined withthe Monte-Carlo method. Finally, the SSOTS method developed in this papershows an excellent computational accuracy, and therefore presents an importantadvance towards computationally efficient multiscale modeling frameworksconsidering microstructure uncertainties.
Keywords: Mechanical properties; stochastic second-order two-scale method; random interpenetrating phase composites; strength properties.